Mental Health and Social Inclusion: The Human Rights challenges Among LGBT Community in Mainland China - Chan, Alex Siu Wing (European Journal of Applied Sciences, 2022)
Mainland China has the world’s largest population and is also home to the LGBT community’s highest proportion. Despite the legalization of homosexuality in mainland China in 1997, the LGBT community faces discrimination in their daily activities. The recent studies carried out in 2019 and 2020 on the LGBT community’s prejudice in mainland China showed that these individuals still encountered rejection despite its legalization two decades ago. Rejection starts from family, continuing to school, workplaces, and religious centers. The Burki (2017) study revealed that the majority of LGBT individuals live in their cocoons, fear of discrimination, and the implications of those factors may negatively impact their mental and physical health. In some LGBT communities, marriage is a form of social conformity. Despite the fact that some heterosexual individuals are likely to interact with homosexuals, many are highly opposed to allowing their children to associate with the LGBT community. It is expected that everyone conforms to the norms that are acceptable to the majority of the population. While the available research has led to greater acceptance of the LGBT community, more work is needed, particularly when it comes to recognizing homosexuals by the government. Therefore, the purpose of this paper is to increase awareness of LGBT mental health and promote social inclusion.